Piracy in the Eastern Mediterranean - Mylonakis, Leonidas. (London)
xv, 192 sayfa
Keywords: “Did British, French and Russian gunboats pacify the notoriously corsair-infested waters of the Eastern Mediterranean? This book charts the changing rates and nature of piracy in the Eastern Mediterranean in the nineteenth century. Using Ottoman, Greek and other archival sources, it shows that far from ending with the introduction European powers to the region, piracy continued unabated. The book shows that political reforms and changes in the regional economy caused by the accelerated integration of the Mediterranean into the expanding global economy during the third quarter of the century played a large role in ongoing piracy. It also considers imperial power struggles, ecological phenomena, shifting maritime trade routes, revisions in international maritime law, and changes in the regional and world economy to explain the fluctuations in violence at sea“ -- Yayıncı.